A quality index for detection of atypical elements (outliers) - Kulczycki, Piotr; Franus, Krystian; Charytanowicz, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski)
Besides clustering and classification, detection of atypical elements (outliers, rare elements) is one of the most fundamental problems in contemporary data analysis. However, contrary to clustering and classification, an atypical element detection task does not possess any natural quality (performance) index.
Keywords: data analysis; atypical elements; outliers; rare elements; quality (performance) index